2009
DOI: 10.1016/j.joca.2008.12.012
|View full text |Cite
|
Sign up to set email alerts
|

Do HOXB9 and COL1A1 genes play a role in congenital dislocation of the hip? Study in a Caucasian population

Abstract: Our study did not support an association between HOXB9 and COL1A1 and CDH in our population. These negative findings were obtained by population- and family-based designs. Analysis of the genetic component of CDH should focus on other candidate genes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 39 publications
0
21
0
1
Order By: Relevance
“…In a small pilot genetic association study, Rouault and coinvestigators recently found no association of DDH with HOXB9 and COL1A1 in a small regional French population in which the incidence of this disorder was elevated [27]. Although an intriguing preliminary observation, the limited geographic sampling of this study does not preclude either of the genes playing a causative role in other populations.…”
Section: Discussionmentioning
confidence: 50%
“…In a small pilot genetic association study, Rouault and coinvestigators recently found no association of DDH with HOXB9 and COL1A1 in a small regional French population in which the incidence of this disorder was elevated [27]. Although an intriguing preliminary observation, the limited geographic sampling of this study does not preclude either of the genes playing a causative role in other populations.…”
Section: Discussionmentioning
confidence: 50%
“…The Independent-Samples T test was used to determine differences according to age, and the chisquare or Fisher's exact test was performed to calculate the clinical parametric distributions. Unconditional logistic regression analysis models were used to evaluate the relationships between different genotypes and disease risk [Odds ratios (OR), 95% confidence intervals (95% CI)] adjusted by age and gender [23,24]. To account for multiple testing, Bonferroni correction was applied.…”
Section: Methodsmentioning
confidence: 99%
“…Homeobox B9 (HoxB9), a transcription factor, belongs to the products of homeobox (Hox) transcription factor gene family and is known to regulate transcription of CD56 and to promote tumorigenicity and metastasis in some malignancies [16][17][18][19]. Its expression is critical for embryonic segmentation and limb patterning during embryogenesis, and dysregulated expression has been observed in certain malignancies [20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%